2022
DOI: 10.3389/fimmu.2022.849592
|View full text |Cite|
|
Sign up to set email alerts
|

Pan-Cancer Analysis Shows That ALKBH5 Is a Potential Prognostic and Immunotherapeutic Biomarker for Multiple Cancer Types Including Gliomas

Abstract: BackgroundAlkB homolog 5 (ALKBH5) is a N6-methyladenosine (m6A) demethylase associated with the development, growth, and progression of multiple cancer types. However, the biological role of ALKBH5 has not been investigated in pan-cancer datasets. Therefore, in this study, comprehensive bioinformatics analysis of pan-cancer datasets was performed to determine the mechanisms through which ALKBH5 regulates tumorigenesis.MethodsOnline websites and databases such as NCBI, UCSC, CCLE, HPA, TIMER2, GEPIA2, cBioPorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 76 publications
1
42
0
Order By: Relevance
“…In diabetic retinopathy, the change of ALKBH5 expression could cause m6A modi cation to be dysfunctional (72). In cancers, it was shown that ALKBH5 and its related genes were enriched in the in ammatory, metabolic, and immune signaling pathways in gliomas, suggesting that ALKBH5 might be a potential treatment for this disease (73). However, there is no relative study to explore how ALKBH5 works in PCOS through in ammations in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic retinopathy, the change of ALKBH5 expression could cause m6A modi cation to be dysfunctional (72). In cancers, it was shown that ALKBH5 and its related genes were enriched in the in ammatory, metabolic, and immune signaling pathways in gliomas, suggesting that ALKBH5 might be a potential treatment for this disease (73). However, there is no relative study to explore how ALKBH5 works in PCOS through in ammations in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…The genes without ensemble gene ID were removed. Next, the results were visualized as volcano plots through the Sangerbox platform 2 ( 24 ). Then, A Venn diagram was created by an online tool 3 to confirm the overlapping DEGs of the two datasets.…”
Section: Methodsmentioning
confidence: 99%
“…TIMER and TISIDB ( https://cis.hku.hk/TISIDB/index.php ) [ 35 ] are two classic online sites for immunoassays with powerful immune infiltration analyses, which we applied for the evaluation of immune lymphocyte infiltration. Sangerbox ( http://sangerbox.com/Tool ) is a powerful website for raw letter analysis [ 36 ]; this tool used its GO and KEGG analysis functions. The list of extended full names and abbreviations of tumors are provided in Supplementary File 1.…”
Section: Methodsmentioning
confidence: 99%